2015
DOI: 10.1038/nchem.2366
|View full text |Cite
|
Sign up to set email alerts
|

A manganese catalyst for highly reactive yet chemoselective intramolecular C(sp3)–H amination

Abstract: C—H bond oxidation reactions underscore the existing paradigm wherein high reactivity and high selectivity are inversely correlated. The development of catalysts capable of oxidizing strong aliphatic C(sp3)—H bonds while displaying chemoselectivity (i.e. tolerance of more oxidizable functionality) remains an unsolved problem. Herein, we describe a catalyst, manganese tert-butylphthalocyanine [Mn(tBuPc)], that is an outlier to the reactivity-selectivity paradigm. It is unique in its capacity to functionalize al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
137
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(149 citation statements)
references
References 45 publications
5
137
0
3
Order By: Relevance
“…On the other hand, Ru and Fe catalysts furnished 2 with varying degrees of selectivity. 8c,20 These results fit the prevailing NT mechanistic paradigm, where catalysts proceeding via stepwise H-transfer/radical recombination (S-HT:RR) tend to show higher kinetic isotope effect (KIE) values (Scheme 1B) and favor amination of weaker C−H bonds (BDE: 2° benzylic C− H ~ 85 kcal/mol; 3° alkyl C(sp 3 )−H ∼ 95 kcal/mol).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…On the other hand, Ru and Fe catalysts furnished 2 with varying degrees of selectivity. 8c,20 These results fit the prevailing NT mechanistic paradigm, where catalysts proceeding via stepwise H-transfer/radical recombination (S-HT:RR) tend to show higher kinetic isotope effect (KIE) values (Scheme 1B) and favor amination of weaker C−H bonds (BDE: 2° benzylic C− H ~ 85 kcal/mol; 3° alkyl C(sp 3 )−H ∼ 95 kcal/mol).…”
Section: Resultssupporting
confidence: 67%
“…22 As with all metal-catalyzed NT reactions reported to date, the negative ρ value indicates a buildup of positive charge in the transition state (TS). 13,17a,20 These results imply an earlier TS for reactions catalyzed by Ag(tpa)OTf, as compared to other catalysts proceeding via stepwise NT; however, the exact reasons for these mechanistic differences are currently unclear. 17e …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Developing iron catalysts for sp 3 C–H amination is of particular interest due to the high abundance and low toxicity of iron484950. Although most Fe-catalysed C–H amination reactions use sulfamides or azides as a nitrogen source4546485051, we report here the first example of using aniline as a nitrogen source. Heating aniline with neat substrates such as indane, tetraline and cyclohexene gave a C–H aminated product in 41–53% yield with UiO-FeBr (2–10 mol% Fe, Table 4 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 98%
“…9 More recently, it has been shown that the chemoselectivity of nitrene transfer can be altered to favor C‒H insertion by changing the metal identity to Ru, Co, Mn, or Fe, which results in a change from a concerted to a stepwise nitrene transfer event. 3,4b,5,8 …”
Section: Introductionmentioning
confidence: 99%